Coagulant from banana stem juice for treatment of obstinate spent coolant / Habsah Alwi - Alwi, Habsah (2007)
Coagulation is one of very common processes in the water and wastewater treatment. An organic polymer Polyaluminium Chloride (PAC) and inorganic salt Aluminium Sulphate (Alum) are the most widely used coagulants in water treatment. In order to reduce the harmful of chemical coagulants, the naturally source products that are easily available and abundantly left without significant usage has been investigated and discovered. Banana stem waste is the abundantly available agricultural wastes in tropical and subtropical countries. Pulping of banana fiber is a new discovery and now banana stem has been enter to a new era as a cheaply and easily available for wastewater treatment. The natural polymer that available in the juice of the banana stem juice has been acted as the polymer that binds together the floc for easy sedimentation through coagulation and flocculation process. Jar Test method was used to conduct the coagulation process for spent coolant from camera lens manufacturing industries. Coolant can be recycled several times but it will lose the ability to reduce heat, remove excessive material, lubricating and shaping the lens. Currently, the treatment of spent coolant is using coolant distillation method. Cost of the machines and the energy consumption for this treatment are high and expensive. It is discovered that the juice has successfully removed 80.1% of COD, 84.1% for suspended solid removal and turbidity 98.5% of spent coolant through coagulation process. Inulin, the long chain and part of carbohydrate are found in the juice that might be acting as polymer to bind the suspended solid and resulted in biodegradable sludge. The biodegradable sludge that been produced can be reduced by using the Biomass Extract that contains microorganisms. The microorganism has reduced 7.5% total weight of the sludge by digesting the biodegradable sludge into watersoluble molecules and biogas.